2006
DOI: 10.1590/s0066-782x2006001900010
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da pressão arterial em bombeiros militares filhos de hipertensos através da monitorização ambulatorial da pressão arterial

Abstract: Objective: To evaluate the influence of family history of systemic arterial hypertension (FSAH) on the effect of stress from work in Uniformed Firefighters (BMCs) through Ambulatory Blood Pressure Monitoring (ABPM). Methods:A prospective case-control study. Sixty-six healthy BMC underwent ABPM during 12 hours of work at the Communication Center (CC). Thirty-four had hypertensive parents (group 1) and thirty-two had normotensive parents (group 2).Results: Group I differed from group 2 in that it showed higher m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
(41 reference statements)
0
1
0
2
Order By: Relevance
“…Porém, estudos com população de trabalhadores específicos como bombeiros e médicos usaram a MAPA para avaliar a pressão arterial e os resultados mostraram elevações significativas da pressão arterial durante o período de trabalho. 7,8 A elevação da pressão arterial pode acarretar aumento do risco cardiovascular entre esses profissionais. A exposição crônica de indivíduos suscetíveis a condições de trabalho estressantes, pode ser responsabilizada por aumentos pressóricos persistentes e significativos, conduzindo ao quadro hipertensivo.…”
Section: Introductionunclassified
“…Porém, estudos com população de trabalhadores específicos como bombeiros e médicos usaram a MAPA para avaliar a pressão arterial e os resultados mostraram elevações significativas da pressão arterial durante o período de trabalho. 7,8 A elevação da pressão arterial pode acarretar aumento do risco cardiovascular entre esses profissionais. A exposição crônica de indivíduos suscetíveis a condições de trabalho estressantes, pode ser responsabilizada por aumentos pressóricos persistentes e significativos, conduzindo ao quadro hipertensivo.…”
Section: Introductionunclassified
“…These results reinforce the findings of previous research that proved that professions that are characterized with high mental workload or intellectual engagement or that are related to feelings of anxiety and mental exhaustion, provide greater increases in BP so it tends to be higher during the exposure to the occupational ecology as compared with the BP at home or during other daily routines (Couto, Vieira & Lima, 2007). Other studies found that activities that require mental effort (such as teaching) deeply influence BP variability (Schnall, Landsbergis, Warren & Pickering, 1992;Mattos, Mattos, Toledo & Filho, 2006). Other research identified that the sense of responsibility towards the people with whom one works may also be directly related to the increase in BP (Ramos, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Estima-se que 20% dos casos de câncer gastrointestinal, 10% dos casos de acidente vascular cerebral e 30% das doenças cardíacas estão relacionadas ao consumo irregular de hortaliças, indicando que a má ingestão desses alimentos é responsável por cerca de 5% de óbitos por ano em todo o mundo (WHO, 2002;IBGE, 2010;Brasil, 2014;Coelho, 2014). Portanto, considera-se que o consumo adequado de hortaliças previne doenças causadas pela má nutrição, sendo mais econômico que o tratamento com o uso de medicamentos (Palma et al, 2009;Mattos et al, 2010;Pereira;Pereira, 2016).…”
Section: Introductionunclassified